Dynamic analysis of a deforming membrane by digital holographic interferometry - Budini, Nicolas (2015)
In this work we performed an analysis of the deformations suffered by a membrane by means of the non-invasive nor destructive digital holographic interferometry technique (DHI). This technique consists in recording holograms of an object and combining their numerical reconstructions to detect small deformations, displacements or oscillations of the entire object or parts of it. Depending on the experimental setup and the wavelength used for illumination, it is possible to detect variations below the magnitude of the wavelength used. We induced controlled deformations of a plastic membrane by heating the air inside a hermetic chamber with a resistor. By matching the frequency of the induced perturbation with the rate at which holograms are acquired, we could analyze in detail and dynamically the deformation of the membrane. We performed experiments and compared the results with numerical simulations to describe the actual deformation of the membrane. With these results we aim to set the basis for developing a pressure sensing device based in DHI. There are several issues concerning the sensitivity of this technique, namely: it is able to detect really small deformations, displacements or oscillations and, therefore, it becomes diffcult to isolate external noise influencing the observations.